Rat Population Increase And Damage To Rice Plantations With Different Irrigation Systems In Wajo Regency, South Sulawesi Province - Ummu Haddina; Swastiko Priyambodo; Dadan Hindayana (Asian Journal of Social and Humanities, 2023)
One of the rice producing regions in Indonesia is South Sulawesi. Wajo Regency is the second highest rice producing area in South Sulawesi, after Bone Regency. Based on the irrigation system, rice cultivation in Wajo Regency consists of technical irrigation, rainfed rice fields, and rice cultivation or dry land. Agriculture with various irrigation systems has an impact on pest population levels and the intensity of attacks. The decline in rice productivity is caused by many factors, one of which is the attack of rice rat pests that occur in several areas in Wajo Regency. There are several techniques and strategies for field rat management, ranging from sanitation, technical culture or plant cultivation, mechanical, biological, and chemical physical. All techniques and strategies of rice rat management must be applied integrated, continuously, and together in one stretch. This study aims to measure the potential presence of rice rats in several irrigation systems in Wajo Regency (irrigation, rainfed rice fields, and dryland rice), analyze the management of rice rats carried out by farmers, and the factors that affect it. The method used is observing rice planting patterns based on irrigation systems, estimating the population level of rice rats with single live traps and the level of attack on several rice planting irrigation systems. Likewise, rice rat population management in several rice planting irrigation systems, data analysis, and economic analysis. The result of this study is that the highest estimate of rats is in dryland rice plantations. The intensity of rat attacks was highest in dry land Pr>F 0.045 the area of attack was highest in rainfed land Pr>F was 0.0171, for intensity and area of attack in generative phase 1. The success of cultivation in dry land was 16.3% in generative phase 1 which was 16.48%. The presence of rats correlates both the intensity of the attack and the area of each addition of rats will increase the intensity of the attack by 0.155% and the area of attack by 0.308%.